1991
DOI: 10.1136/thx.46.3.184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 5-lipoxygenase inhibitor on leukotriene generation and airway responses after allergen challenge in asthmatic patients.

Abstract: The effect of a single oral dose (800 mg) of zileuton (A-64077), a specific 5-lipoxygenase inhibitor, on the early and late airway responses to inhaled allergen was studied in a randomised, double blind, placebo controlled, and crossover trial in nine subjects with atopic asthma. Leukotriene generation was also assessed in vivo by measuring urinary leukotriene (LT) E4 excretion, and ex vivo by measuring calcium ionophore stimulated whole blood LTB4 production. Zileuton almost completely inhibited ex vivo LTB4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(64 citation statements)
references
References 25 publications
4
59
1
Order By: Relevance
“…within 1 h) increased FEV1 by ~0.35 L in patients with an FEV1 of ~57-60% pred [12]. Such improvement was not observed in other studies [7,8] or in the present patients, presumably because the FEV1 was close to its predicted value in these studies. Thus, an increase in airway calibre is unlikely to be the explanation for the reduced responses to histamine and UNDW challenge after zileuton found in the present study.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…within 1 h) increased FEV1 by ~0.35 L in patients with an FEV1 of ~57-60% pred [12]. Such improvement was not observed in other studies [7,8] or in the present patients, presumably because the FEV1 was close to its predicted value in these studies. Thus, an increase in airway calibre is unlikely to be the explanation for the reduced responses to histamine and UNDW challenge after zileuton found in the present study.…”
Section: Resultscontrasting
confidence: 52%
“…One of these drugs, zileuton (N-1-(benzo(b)thien-2-ylethyl)-N-hydroxyurea), an inhibitor of the 5-lipoxygenase pathway, has been shown to be efficacious in patients with asthma [3][4][5][6]. Single-dose studies have shown an attenuation of the asthmatic response to cold dry air [7], but not after allergen challenge [8]. In aspirin-sensitive asthmatics, 2.4 mg zileuton daily for 1 week prevented the fall in forced expiratory volume in one second (FEV1) in response to ingestion of aspirin [9].…”
Section: Effects Of Single-dose Zileuton On Bronchial Hyperresponsivementioning
confidence: 99%
“…Leukotriene antagonists, including 5-lipoxygenase inhibitors such as Zileuton, have been proven effective as anti-asthmatic agents and are widely used in clinical practice [11][12][13][14]. Zileuton is considered a relatively safe agent.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] A number of anti-leukotriene drugs, which act as biosynthesis inhibitors or receptor antagonists of the LTs, have proved to be of benefit to treat asthmatic reactions. 8,9 Peptide leukotriene metabolites are excreted into urine as LTE4 in humans, 10 and urinary LTE4 may therefore reflect the status of LTs in the whole body. Quantitative determination of LTE4 in urine may thus be useful for evaluation of the effects of anti-leukotriene drugs in various diseases, and there is a need for an accurate and reproducible analytical method for determination of LTE4 in urine.…”
Section: Introductionmentioning
confidence: 99%